Voltage and Frequency Control of Variable Speed Induction Generator using One Cycle Control Technique - T. Elango; A.Senthil Kumar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
Induction generators are widely used to extract the energy from renewable sources, particularly as a wind power generator either grid connected or isolated operation. The problem associated with stand-alone mode operation is voltage and frequency control. An electronic load controller is used for frequency / voltage control. It uses PI controller to generate the gating signal for the DC chopper. This method has the fault of bad dynamic response and thedistortion of output voltage at zero-crossing. To overcome the defect of PI controller when steady state error is equal to zero, a one cycle control technique suggested and implemented. Simulation of wind driven self-excited induction generator (SEIG) performance is studied and results are discussed.